Cadmium exposure induces pancreatic β-cell death via a Ca2+-triggered JNK/CHOP-related apoptotic signaling pathway. (1st September 2019) - Huang, Cheng-Chin; Kuo, Chun-Ying; Yang, Ching-Yao; Liu, Jui-Ming; Hsu, Ren-Jun; Lee, Kuan-I; Su, Chin-Chuan; Wu, Chin-Ching; Lin, Ching-Ting; Liu, Shing-Hwa; Huang, Chun-Fa
Graphical abstract: Highlights: Cadmium (Cd) inhibits pancreatic β-cell insulin secretion and induces apoptosis. Cd causes β-cell apoptosis via JNK activation downstream-mediated CHOP pathway. [Ca 2+ ]i plays a crucial role in Cd-induced β-cell dysfunction and apoptosis. Abstract: Cadmium (Cd) is known to be ranked the 7 th hazardous substance in the Substance Priority List by Agency for Toxic Substances and Disease Registry. The experimental and epidemiological data have suggested that Cd is linked to the development of diabetes mellitus (DM). The molecular mechanism of Cd on the pancreatic β-cell cytotoxicity still remains unclear. Evidence has pointed toward that Ca 2+ is an important regulator of toxic insult-induced β-cell cytotoxicity. The role of Ca 2+ in the Cd-induced β-cell cytotoxicity is still unknown. In this study, we found that Cd exposure significantly inhibited insulin secretion and cell viability in the pancreatic β-cell-derived RIN-m5F cells. Cd exposure induced apoptotic events, including the increased populations of apoptotic cells and sub-G1 hypodiploid cells, and caspase-3/-7/-9 and poly (ADP-ribose) polymerase (PARP) activation, which largely depended on the activation of c-Jun N-terminal kinase (JNK) and C/EBP homologous protein (CHOP). Transfection with siRNAs for JNK and CHOP or pretreatment with specific pharmacological inhibitor of JNK (SP600125) in β-cells effectively prevented the Cd-induced insulin secretion dysfunction and apoptosis. JNK-specific siRNA dramatically suppressed Cd-induced JNK phosphorylation and CHOP protein expression, but JNK phosphorylation could not be inhibited by CHOP-specific siRNA. Furthermore, Cd exposure significantly increased the intracellular calcium ([Ca 2+ ]i ) levels. Buffering the Ca 2+ response with BAPTA/AM effectively abrogated the Cd-induced [Ca 2+ ]i elevation, insulin secretion dysfunction, apoptosis, and protein expression of JNK phosphorylation and CHOP activation. Taken together, these findings demonstrated that Cd exposure exerts β-cell death via a [Ca 2+ ]i -dependent JNK activation-activated downstream CHOP-related apoptotic signaling pathway.